Longitudinal Magnetomorphic Effect in Indium Films - de la Cruz, F.; de la Cruz, M.E.; Cotignola, J.M. (American Physical Society, 1967)
Fil: de la Cruz, F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina